A Corpus of Anglo-Saxon and Medieval Pottery from Lincoln - Naylor, Victoria (Historic England, 2006)
This volume reports on the Anglo-Saxon and Medieval pottery found during various archaeological excavations in the city from 1970 until 1987. The authors present a city-wide pottery classification system and analyse the sequence of pottery types through time and at numerous sites. They make extensive use of petrological analysis, including the study of over 600 thin-sections. These have been used to characterise the local clay and temper sources exploited by Lincoln potters and to identify wares made in the vicinity of the city, those made elsewhere in the county of Lincolnshire, and to identify regional and foreign imports. The volume is arranged by pottery types, illustrated by typical and unusual examples and accompanied by descriptions of their visual appearance, petrological characteristics, source, forms, decoration and dating evidence.